2019
DOI: 10.1055/a-0895-5275
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Periodontitis is a Risk Factor of Renal Dysfunction in Patients with Type 2 Diabetes

Abstract: Background This study explores the association between chronic periodontitis and renal dysfunction in type 2 diabetic mellitus (T2DM) patients. Methods An observational study was conducted in 169 T2DM patients with chronic periodontitis. Patients were divided into 2 groups according to presence of normal renal function (n=111) and renal dysfunction (n=58), and oral health behavior-related variables were obtained by questionnaire. Periodontal status was examined, and pocket probing depth (PD), clinical attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…Studies have shown that periodontitis contributes to the development and progression of DN. Our previous study showed that percent of sites with PD ≥4 mm was positively associated with risk for renal dysfunction in patients with DM 26 . Accordingly, in this study, PD and percent of sites with PD ≥4 mm were positively correlated with ACR in T2DN patients with periodontitis and dyslipidemia, suggesting a relationship between periodontal inflammation, blood lipid control, and renal dysfunction among T2DN patients.…”
Section: Discussionsupporting
confidence: 64%
“…Studies have shown that periodontitis contributes to the development and progression of DN. Our previous study showed that percent of sites with PD ≥4 mm was positively associated with risk for renal dysfunction in patients with DM 26 . Accordingly, in this study, PD and percent of sites with PD ≥4 mm were positively correlated with ACR in T2DN patients with periodontitis and dyslipidemia, suggesting a relationship between periodontal inflammation, blood lipid control, and renal dysfunction among T2DN patients.…”
Section: Discussionsupporting
confidence: 64%
“…The results of our research did not show significant difference in periodontal status between the two groups. There are probably several reasons for this, one of them being the fact that the control group comprised subjects with only one to two grades of milder CKD, and this difference may not be sufficient to affect periodontal status significantly 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic periodontitis (CP) is an inflammatory and destructive disease with multiple microbial sources and is characterized by gingival inflammation, periodontal attachment loss, alveolar bone resorption and periodontal pocket formation [ 6 , 7 ]. The natural history of CP slowly progresses from the early gingivitis stage to irreversible severe periodontitis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%